The root‐invading pathogen Fusarium oxysporum targets pattern‐triggered immunity using both cytoplasmic and apoplastic effectors. Issue 5 (18th May 2020) - Tintor, Nico; Paauw, Misha; Rep, Martijn; Takken, Frank L. W.
Summary: Plant pathogens use effector proteins to promote host colonisation. The mode of action of effectors from root‐invading pathogens, such as Fusarium oxysporum ( Fo ), is poorly understood. Here, we investigated whether Fo effectors suppress pattern‐triggered immunity (PTI), and whether they enter host cells during infection. Eight candidate effectors of an Arabidopsis‐infecting Fo strain were expressed with and without signal peptide for secretion in Nicotiana benthamiana and their effect on flg22‐triggered and chitin‐triggered reactive oxidative species (ROS) burst was monitored. To detect uptake, effector biotinylation by an intracellular Arabidopsis‐produced biotin ligase was examined following root infection. Four effectors suppressed PTI signalling; two acted intracellularly and two apoplastically. Heterologous expression of a PTI‐suppressing effector in Arabidopsis enhanced bacterial susceptibility. Consistent with an intracellular activity, host cell uptake of five effectors, but not of the apoplastically acting ones, was detected in Fo ‐infected Arabidopsis roots. Multiple Fo effectors targeted PTI signalling, uncovering a surprising overlap in infection strategies between foliar and root pathogens. Extracellular targeting of flg22 signalling by a microbial effector provides a new mechanism on how plant pathogens manipulate their host. Effector translocation appears independent of protein size, charge, presence of conserved motifs or the promoter driving its expression.